Adaptive Reuse Strategies for Historic Aesthetic Elements and Interior Design: A Systematic Literature Review - Donny Trihanondo; Tri Haryotedjo (Yupa: Historical Studies Journal, 2025)
Abstract Adaptive reuse is a key strategy for conserving heritage buildings while preserving cultural and historical values. Despite its importance, research on integrating adaptive reuse with interior aesthetic elements like reliefs, sculptures, and ornaments remains limited. This study addresses the gap through a systematic literature review, exploring how these elements can be preserved to extend building lifespans and improve user experiences. Case studies from diverse cultural contexts highlight the critical role of interior aesthetics in adaptive reuse. The findings call for collaboration among architects, artists, and conservation experts to ensure holistic and sustainable preservation. Recommendations are provided to harmonize adaptive reuse with conserving interior aesthetics, safeguarding the integrity and relevance of heritage buildings.